PROBLEMATIKA DALAM MEWUJUDKAN CITA-CITA NKRI: PERMASALAHAN DAN ALTERNATIF PENYELESAIAN REFORMASI PENDIDIKAN NASIONAL - H.A.R. Tilaar (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
Indonesia has been making reforms in many aspects for more than eight years, but there is no strong indicator to show the multi dimension crisis ending soon. This article focuses the discussion on education aspect particularly its role in improving the quality of life of Indonesian people. In the line with the amendment of Constitution of 1945, the national education should have clear and appropriate vision and strategic planning to achieve the national objectives of education. This article emphasizes the role of local governments in implementing basic education program both in long and short terms.